Temporalisation et diffusion des savoirs - Marie-Pierre Chopin (Éducation et Socialisation)
The definitions of the field as « history made space » and of the habitus as « history embedded » underline how the practice, for Bourdieu, is concerned by the question of time. This historicized conception of action is particularly useful for the study of the phenomena of the knowledge’s diffusion, especially about the management of the teaching, in situ and on line. Exceeding a provisional conception of time (time as a capital) and dismissing both the theme of the planning and the one of the improvisation in the teaching practices, we show that the Bourdieu’s theory contributes to renew the way of thinking the time in the transmission, by developing a constitutive conception about it. On the basis of a research leaded among 8 classes of CM2, we show that this conception helped the apparition of a new concept for the study of the teaching phenomena : the didactic visibility. This concept will be linked here with a central idea of the Bourdieu’s theory : the one protention.